The Effect of Equal Channel Angular Pressing on Coarsening Kinetics of AZ80–0.2Y–0.15Ca Alloy in Semisolid State. Issue 12 (23rd August 2020) - Fan, Lingling; Zhou, Mingyang; Ren, Lingbao; Li, Houyi; Zhang, Hongtao; Lu, Tianhui; Liu, Chongliang; Quan, Gaofeng
Abstract : Semisolid samples of the AZ80–0.2Y–0.15Ca wt% (AZ80M) magnesium alloy are fabricated using equal channel angular pressing (ECAP) followed by semisolid isothermal heating treatment. The effect of the number of ECAP passes on the coarsening dynamics of the alloy at different semisolid temperatures is investigated. The results show that as the number of ECAP passes increases, the coarsening rate constant ( K ) shows a similar trend downward and then upward at different temperatures. And the K value of the sample after three passes of ECAP processing (3P) is the lowest, which is primarily attributed to the maximum proportion of high‐angle grain boundaries (HAGBs) and the most uniform grain size in the 3P sample. At high solid fractions, a high proportion of HAGBs hinders the coalescence of the adjacent solid grains. At low solid fractions, uniform and fine grains result in insufficient driving force for the Ostwald ripening process. These lead to the lowest K value in the 3P sample. Abstract : Herein, it is reported that the significant influence of equal channel angular pressing passes on the coarsening rate constant ( K ) mainly results from its impact on the grain size and the proportion of high‐angle grain boundaries in the deformed sample. In addition, the rise of isothermal temperature leads to the transformation of the coarsening mechanism, which also affects the variation of the K value.